ETCHED SILICON COATED WITH POLYANILINE AS THE ANODE FOR LITHIUM-ION BATTERY - Haidar Hamid, Faiq
Lithium Ion-Batteries have surpassed previously competitive battery chemistry (lead-acid and nickel metal hydride), but still require more improvement. To enhance the energy capacity, materials that enable more lithium ions to be stored in their structure are needed to be introduced as anode active material. Silicon is one of the most promising anode materials due to its superior theoretical capacity of 4200 mAh g-1 for Li4.4Si, ten times larger than the theoretical capacity of commonly used graphite. However, silicon possesses high volume expansion (300%) that will generate interfacial stress which causes the anode active material to pulverize and continuous formation of Solid Electrolyte Interphase (SEI) layer. In this research, silicon particle is engineered to form an etched structure. This structure then being coated with thin conductive polyaniline film to improve the conductivity. Silicon micro-powder is processed with a high-energy vibrational ball mill to reduce the particle size (SiBM20h sample). The etched structure is obtained by a metal-assisted chemical etching reaction (SiMACE sample). Ag+ ion is deposited on the surface of the silicon powder to grind the surface following the electrophoretic movement of Ag particle. A conductive polymer coating is obtained from the oxidative-additive polymerization reaction of aniline monomer (SiMACEPANI sample). The XRD characterization shows no impurities after the milling and etching process. The FTIR spectroscopy confirms the formation of polyaniline. The anode active material was successfully assembled into a half-cell configuration CR2032 coin battery. Electrochemical impedance characterization reveals that thin polyaniline film could lower the SEI resistance and improve the charge transfer on the sample. The Galvanostatic Charge Discharge test resulted in 69.50% specific capacity retention for SiMACEPANI, followed by 52.03% and 26.95% for SiMACE and SiBM20h samples after 100 cycles.